The transient response of atmospheric and oceanic heat transports to anthropogenic warming - He, Chengfei; Liu, Zhengyu; Hu, Aixue (Nature climate change, 2019)
Model projections of the near-future response to anthropogenic warming show compensation between meridional heat transports by the atmosphere (AHT) and ocean (OHT) that are largely symmetric about the equator 1 – 3 , the causes of which remain unclear. Here, using both the Coupled Model Intercomparison Project Phase 5 archive and Community Climate System Model version 4 simulations forced with Representative Concentration Pathway 8.5 to 2600, we show that this transient compensation—specifically during the initial stage of warming—is caused by combined changes in both atmospheric and oceanic circulations. In particular, it is caused by a southward OHT associated with a weakened Atlantic Meridional Overturning Circulation, a northward apparent OHT associated with an ocean heat storage maximum around the Southern Ocean, and a symmetric coupled response of the Hadley and Subtropical cells in the Indo-Pacific basin. It is further shown that the true advective OHT differs from the flux-inferred OHT in the initial warming due to the inhomogeneous responses of ocean heat storage. These results provide new insights to further our understanding of future heat transport responses, and thereby global climatic processes such as the redistribution of ocean heat. The compensation between atmospheric and oceanic heat transports under anthropogenic warming can be linked to the combined impact of Atlantic Meridional Overturning Circulation weakening, perturbations to Southern Ocean heat storage, and coupled responses of the Hadley and Subtropical cells.